Paleontología y geoquímica de la formación Agua de la Zorra, Triásico medio a superior de la Cuenca Cuyana, provincia de Mendozza - Pedernnera, Tomás (2017)
The Agua de la Zorra Formation deposits representa deltaic-lacustrine system. The unit ineludes Corystospermales, together with Equisetales and section would correspond to a delta deposit with scarce ke - rogen; the paleoflora includes complete to fragmented leaves and stems. The upper part would represent prodelta to offshore lacustrine deposits, bearing variable amounts of non-fluorescent amorphous kerogen; the megaflora remains are relatively small size, partially broken and disarticulated. The stacking pattem shows a progressive deepening of the lacustrine system what correlates with an increase upwards of the abundance of organic matter (OM) preserved. The increase of the K/Rb ratio to the top of the section, suggests a terrigenous origin of the kerogen in the deepest horizons ofthe lake. The analysis ofthe Cr/Zr ratio, together with the presence ofV would indicate the existence ofbasic rocks in the provenance area ofthe basin.